2014
DOI: 10.1007/s00280-014-2610-x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of bevacizumab enhances antitumor activity of erlotinib against non-small cell lung cancer xenografts depending on VEGF expression

Abstract: PurposeErlotinib, an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), and bevacizumab, an anti-vascular endothelial growth factor (VEGF) agent, are promising therapies for advanced non-small cell lung cancer (NSCLC). Our study was aimed to determine whether there were conditions under which the addition of bevacizumab would enhance the antitumor activity of erlotinib against NSCLC tumors in vitro and in vivo.MethodsMTS was for NSCLC cell (PC9, 11–18, H1975, H157, H460 and A549) growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 40 publications
5
54
0
Order By: Relevance
“…EGFR-mutated tumors display higher VEGF expression levels than wild-type EGFR tumors (16). EGFR-TKI-resistant tumors also produce greater levels of VEGF, and the amount of VEGF production varies according to the mutation type (17,18). These data may explain the favorable efficacy of Bev-containing chemotherapy in patients with EGFR exon 19 deletions.…”
Section: Discussionmentioning
confidence: 62%
“…EGFR-mutated tumors display higher VEGF expression levels than wild-type EGFR tumors (16). EGFR-TKI-resistant tumors also produce greater levels of VEGF, and the amount of VEGF production varies according to the mutation type (17,18). These data may explain the favorable efficacy of Bev-containing chemotherapy in patients with EGFR exon 19 deletions.…”
Section: Discussionmentioning
confidence: 62%
“…[17][18][19] VEGF and its receptors are frequently overexpressed in human tumors and inhibition of angiogenesis with bevacizumab, a monoclonal antibody that selectively binds to VEGF has shown promising clinical efficacy. [20][21][22][23][24] Multiple studies have shown that high VEGF expression in tumor or in serum is an indicator of prognosis of non-small cell lung cancer and response to anti-angiogenesis. 25,26 As such, VEGF SNP has been extensively investigated for its role in predicting cancer susceptibility, progression and anti-VEGF therapeutic response in subjects with tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of DNR in each tissue was calculated using high-performance liquid chromatography (HPLC) for subsequent determination of its distribution in tissues from the different groups. 23 …”
Section: Determination Of Dnr Concentration By High-performance Liquimentioning
confidence: 99%